Efektifitas Loading Cairan Koloid Terhadap Kejadian Hipotensi Pada Pasien Sectio Caesarea Dengan Spinal Anestesi Di RSD Dr A.Dadi Tjokrodipo Bandar Lampung - Mustika Sari; Galih Pria Pambayun; Ambar Samekto (Pusat Riset dan Inovasi Nasional, 2021)
RSD Dr.A. Dadi Tjokrodipo Bandar Lampung, sectio caesaria patients in the last 3 months of 2021 totaled 40 patients. Hypotension or decrease in Mean Arterial Pressure (MAP) in caesarean section often occur consequence spinal anesthesia due to overall blockade effect on the sympathetic nervous system . Study this aim for This study aims to determine the effect of loading colloid fluid in sectio caesarea patients with spinal anesthesia. Method study qualitative with a descriptive research design is a research that tends to use analysis . Population study 40 patients sectio caesarea with spinal anesthesia at Dr A. Dadi Tjokrodipo Hospital Bandar Lampung with amount sample of 8 patients. From result study